The Prevalence of Undiﬀerentiated Connective Tissue Dysplasia in Senior Students - Mykhailo Protsailo; Volodymyr Dzhyvak; Ihor Krycky; Pavlo Hoshchynskyi; Ihor Horishnyi; Iryna Chornomydz (Lithuanian Sports University, 2023)
Background. Connective tissue dysplasia is an important medical condition requiring attention and research. The aim. To analyse the prevalence of the clinical signs of undiﬀerentiated connective tissue dysplasia among senior students of educational institution. Methods. 110 senior students (average age - 20 years) were examined (females 64 %, males 36 %). Joint hypermobility was assessed according to the Bayton scale, joint hypermobility syndrome according to the Brighton criteria. The main criteria for undiﬀerentiated connective tissue dysplasia and the stigma of dysembryogenesis were studied: ﬂat feet; deformities of the spine, chest; visual impairment etc. The state of the cardiovascular system and gastrointestinal tract was assessed by questioning and anamnestic data. Results. Joint hypermobility was the most common feature of undiﬀerentiated connective tissue dysplasia, accounting for 62.7%. Malocclusion occurred in 36.8% of cases, visual impairment occurred in 32.7%, myopia in 21.8%, astigmatism in 4.5%, strabismus in 3.7%, and a combination of astigmatism and myopia in 2.7%. Abnormalities in the development of the dentition of the jaws were found in 29.1% of students. Deformities of the feet with a decrease in the longitudinal arch were diagnosed in 21.8% and spinal axis deviations in 21%. Conclusions. Undiﬀerentiated connective tissue dysplasia in senior students was most often manifested by joint hypermobility, visual impairment, malocclusion, ﬂat feet, scolytic deformities, and multiple stigmata of dysembryogenesis. Keywords: connective tissue dysplasia, joint hypermobility, diagnostics, students, stigma of dysembryogenesis, rehabilitation.